Hegel e a populaça (Pöbel) (Revista Eletrônica Estudos Hegelianos, 2019)
The object of the article is Hegel’s treatment, especially from his Philosophy of Right, of the negativity of civil society: without arriving at Marx’s later discovery of an insurmountable contradiction between capital and wage labor, Hegel already points, from the observation of the dynamics of economic relations linked to the nascent capitalism, to an uncomfortable polarization between rich and poor, which makes possible the emergence of a subjectivity characteristic of the “rabble,” whose combat Hegel seems to attribute to the corporation. We seek to examine the limits and validity of the diagnosis, as well as the solutions offered by Hegel to the rabble’s problem, from the perspective of contemporary philosophers such as Frank Ruda, Slavoj Žižek and Axel Honneth.